2015
DOI: 10.3109/0886022x.2015.1106847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroid hormone on serum magnesium levels: the neglected relationship in hemodialysis patients with secondary hyperparathyroidism

Abstract: disturbance plays an important role in CKD-MBD and cardiovascular mortality, the interest on magnesium has grown recently. Although much concern focused on the effect of Mg on parathyroid hormone (PTH) levels, however, the influence of PTH on serum Mg levels is nearly unexplored. To evaluate the effect of PTH on serum Mg levels, we first described the relationship between serum Mg and PTH in secondary hyperparathyroidism. Besides, we also monitored the changes of serum Mg concentration after parathyroidectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, Sanda et al [12] stated that PTH could elevate serum magnesium levels by enhancing its gastrointestinal absorption and bone resorption. In 2015, Fang et al [13] documented a case of preoperative hypermagnesemia. They suggested that magnesium liberated by PTH induced excessive osteoclastic bone resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sanda et al [12] stated that PTH could elevate serum magnesium levels by enhancing its gastrointestinal absorption and bone resorption. In 2015, Fang et al [13] documented a case of preoperative hypermagnesemia. They suggested that magnesium liberated by PTH induced excessive osteoclastic bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that magnesium liberated by PTH induced excessive osteoclastic bone resorption. PTX could stimulate hungry bone syndrome, causing a postoperative reduction of serum magnesium, which might be due to the movement of magnesium out of the extracellular space into the cells or to be deposited in the bones [13]. It was suggested that patients on dialysis are largely dependent on the magnesium concentration in the dialysate to maintain their serum magnesium levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, extreme hypomagnesemia immediately after parathyroidectomy and precipitation of acute CPP arthritis in this setting have also been described (21). It has been proposed that hypomagnesemia in the period after parathyroidectomy for hyperparathyroidism is related to the hungry bone syndrome and Mg being driven from the extracellular to the intracellular space (22).…”
Section: Magnesium Disordersmentioning
confidence: 99%
“…In patients with diuretic-induced hypomagnesemia, apart from replacing Mg, switching to a different form of therapy or diuretic should be considered. In patients with hyperparathyroidism, undergoing parathyroidectomy treatment with parenteral Mg replacements to prevent acute CPP arthritis in the post-surgery period should be attempted (22,25).…”
Section: Managementmentioning
confidence: 99%
“…p  < 0.05 was considered to be statistically significant. The basis of calculation of sample size is following, according to previous publications [5], age, and serum Mg-related coefficient β = 0.295. Linear regression module of PASS analysis software was used to calculate the sample size required in this study.…”
Section: Methodsmentioning
confidence: 99%